Hexa-Quad Transformation Control for Hexapod Robot Based on Support Polygon Pattern - Addie Irawan, Hashim; Tan, Yee Yin; Mohd Syakirin, Ramli; Mohd Riduwan, Ghazali; Nonami, Kenzo (2013)
This paper presents a leg reconfigurable technique to optimize the multi-legged robot operation and walking performances. A hexapod-to-quadruped (Hexa-Quad) transformation technique is proposed to optimize hexapod legs on certain situation that need some legs to be disabled as a leg to do other tasks/operations. By separating two legs from the others, hexapod robot is able to be configured as quadruped robot configuration. Quadruped robot configuration is stand within dynamically and statically stable criteria if compare to the hexapod robot that has only statically stable criteria. Thus, it is very crucial to have a stable transformation technique during walking and operation session. Therefore Hexa-Quad is proposed with reference to the defined support polygon that based on its body area. A real-time based model of hexapod robot (4-DOF/leg) control architecture with Hexa-Quad transformation is designed and verified using separated 3D simulators.